(untitled) (Journal of Contemporary Philology, 2024)
In this article, we look into the semantics and pragmatics of the particle zar in the standard Macedonian language, which is used interchangeably with its variant zarem. We argue that zar or zarem is employed in biased polar questions, particularly in contexts where there exists a discrepancy between the speaker’s presupposition and contextual evidence that contradicts it. Our investigation aims to uncover the role of zar/zarem in biased polar questions and determine the discourse functions of zar- questions. To achieve this goal, we conducted an analysis using a sample of questions extracted from contemporary Macedonian prose. The results of our analysis indicate that the particle zar/zarem in biased questions is not obligatory but rather serves to enhance the assertive component at the expense of the inquisitive component in the semantic structure of such questions. This enhancement is reflected in the speaker’s disbelief and surprise regarding the truth of proposition encoded in the question, especially in contradiction contexts. Such semantics enable zar-questions to serve rhetorical purposes or perform indirect claims, thereby functioning as effective persuasion strategies.